The visual perception of emotion from masks. - J Farley Norman; Sydney P Wheeler (PLoS ONE)
Fifty-one adults evaluated visually-perceived emotions from 32 masks. These masks (held in the collection of the Kentucky Museum, located on the campus of Western Kentucky University) were created by artists from a wide variety of cultures spanning multiple continents. Each participant evaluated every mask along six dimensions: happiness, sadness, anger, fear, surprise, and disgust. No previous scientific study has ever studied the general effectiveness of masks (other than Japanese Noh masks) in producing perceptions of human emotion. The results showed that the masks were effective in producing substantial variations in perceived happiness, sadness, anger, fear, surprise, and disgust. The ability of the masks to produce effective perceptions of emotion was due to the artists' inclusion of facial features that reliably signal emotions in everyday life.